Solidarity and strife after the Atlanta spa shootings: A mixed methods study characterizing Twitter discussions by qualitative analysis and machine learning - Criss, Shaniece; Nguyen, Thu T.; Michaels, Eli K.; Gee, Gilbert C.; Kiang, Mathew V.; Nguyen, Quynh C.; Norton, Samantha; Titherington, Eli; Nguyen, Leah; Yardi, Isha; Kim, Melanie; Thai, Nhung; et al. (Frontiers in Public Health, 2023)
Abstract Background: On March 16, 2021, a white man shot and killed eight victims, six of whom were Asian women at Atlanta-area spa and massage parlors. The aims of the study were to: 1) qualitatively summarize themes of tweets related to race, ethnicity, and racism immediately following the Atlanta spa shootings, and 2) examine temporal trends in expressions hate speech and solidarity before and after the Atlanta spa shootings. Methods: A random 1% sample of publicly available tweets was collected from January-April 2021. The analytic sample included 708,933 tweets using race-related keywords. This sample was analyzed for hate speech using a newly developed method for combining faceted item response theory with deep learning to measure a continuum of hate speech, from solidarity race-related speech to use of violent, racist language. A qualitative content analysis was conducted on random samples of 1,000 tweets referencing Asians before the Atlanta spa shootings from January-March 15, 2021 and 2,000 tweets referencing Asians after the shooting from March 17-28 to capture the immediate reactions and discussions following the shootings. Results: Qualitative themes that emerged included solidarity (4% before the shootings vs 17% after), condemnation of the shootings (9% after), racism (10% before vs 18% after), role of racist language during the pandemic (2% vs 6%), intersectional vulnerabilities (4% vs 6%), relationship between Asian and Black struggles against racism (5% vs 7%), and discussions not related (74% vs 37%). The quantitative hate speech model showed a decrease in the proportion of tweets referencing Asians that expressed racism (from 1.4% 7 days prior to the event from to 1.0% in the 3 days after). The percent of tweets referencing Asians that expressed solidarity speech increased by 20% (from 22.7% to 27.2% during the same time period) (p<0.001) and returned to its earlier rate within about two weeks. Discussion: Our analysis highlights some complexities of discrimination and the importance of nuanced evaluation of online speech. Findings suggest the importance of tracking hate and solidarity speech. By understanding the conversations emerging from social media, we may learn about possible ways to produce solidarity promoting messages and dampen hate messages.